Spinal Anaesthesia for Cesarean Section in a Patient with Vascular Type Ehlers-Danlos Syndrome - Jeffrey M. Carness; Mark J. Lenart (Case Reports in Anesthesiology)
We report the administration of spinal anaesthesia for cesarean delivery in a parturient with vascular Ehlers-Danlos syndrome. Parturients who genetically inherit this disorder are at risk for significant morbidity and mortality. Risks during pregnancy include premature labor, uterine prolapse, and uterine rupture. Additionally, such laboring parturients are at increased risk of hemodynamic volatility, vascular stress, and severe postpartum hemorrhage. Instrumented delivery and cesarean delivery bring additional risks. Nonpregnancy-related complications include excessive bleeding, intestinal rupture, cardiac valvular dysfunction, and arterial dissection. Despite the complexity of this condition, literature focusing on specific intraoperative anaesthetic management is sparse.